MSMEs Sales Products Marketing Performance Increasement Based on The Use of QRIS - Harries Arizonia Ismail; Ari Pranaditya; Rita Andini (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
One important financial technology instrument that improves marketing performance is the Quick Response Code Indonesian Standard (QRIS), particularly for Micro, Small and Medium Enterprises (MSMEs). This digital payment technique not only facilitates transactions, but it also aids in bigger marketing efforts, potentially leading to increased customer engagement and company success. The case in Semarang city involving 160 MSMEs by the district. Data analysis technique using Structural Equation Modelling (SEM) with proceed by AMOS 22 version. The results of the research shows that all of the hypothesis including: digital literacy level toward QRIS perceived usefulness, digital literacy level toward QRIS ease of use, QRIS ease of use toward QRIS usefulness, QRIS usefulness toward sales products marketing performance, QRIS ease of use toward sales products marketing performance and digital literacy level toward sales products marketing performance are positively and significant.